Water as a blessing and a transient resource : a call to re-define modern attitudes towards water in light of Job 14:7–12 - Kavusa, Kivatsi Jonathan (Journal for semitics, 2017)
This article explores the ecological potential in Job 14:7-12. The metaphor in Job 14 praises the life-giving potential of water to revive a dead tree before presenting its transient character, similar to human life. The article investigates the question of why the author of Job finds it appropriate to use water and water-related images to contrast the potential of water to revive a dead tree with the transient mortals who disappear at death like great bodies of water in times of drought. Using elements of historical, critical, and literary approaches, as well as metaphor theory, and applying the Earth Bible Principle of intrinsic worth, this article argues that water should not be viewed as a limitlessly renewable resource, but a precious gift requiring responsible management.